Edukasi Budaya Menabung Sejak Dini untuk Mempersiapkan Generasi Mandiri di SD Negeri Sempu Kecamatan Ngebel Kabupaten Ponorogo - Fathu Diin; Yuli Ani Setyo Dewi (Social Science Academic, 2025)
The culture of saving is a habit that must be instilled in students from an early age. The character of students who are still developing is a very effective way to instill a savings culture to shape their character wisely in managing finances. The still low level of financial literacy and the level of student interest in saving encourages the need for socialization and guidance with the aim of educating students to increase their understanding and knowledge about the importance of saving and financial literacy as motivation for students towards financial independence in the future. The socialization activities were carried out in four stages: survey and coordination, planning and preparation of activities, implementation of activities, and evaluation. In its implementation, activities were carried out using lecture and discussion methods. As a result, students showed an increase in understanding and awareness and actively participated in using money wisely, and were able to foster a sense of the importance of saving for the future. Therefore, to improve financial literacy in children, cooperation between various parties is needed, one of which is the role of parents through integrated and continuous supervision and guidance activities.